Аналіз досліджень щодо соціального розвитку старопромислових регіонів - Яковлєва, Ю. (Культура народов Причерноморья, 2013)
Аналіз наукових праць географів дає підстави стверджувати, що ступінь вивченості
сучасного стану та розвитку старопромислових регіонів близький до нульового, треба також
зазначити, що більше уваги проблемам розвитку цих територій традиційно приділяють економісти. Й
хоча в останні роки є певні зрушення в напрямку дослідження старопромислових регіонів окремими
географами, багато аспектів їх розвитку з точки зору суспільно-географічних досліджень залишаються
без уваги, а саме: особливості соціального розвитку міських та сільських територій старопромислових
регіонів, визначення цілей, індикаторів та чинників цього процесу.
Ключові слова: соціальний розвиток, старопромислові регіони, суспільно-географічні дослідження,
депресивні регіони. Анализ научных работ географов дает основание утверждать, что степень изученности
современного состояния и развития старопромышленных регионов близка к нулевой, нужно также
отметить, что больше внимания проблемам развития этих территорий традиционно уделяют
экономисты. И хотя в последние годы имеются определенные сдвиги в направлении исследования
старопромышленных регионов отдельными географами, многие аспекты их развития с точки зрения
общественно-географических исследований остаются без внимания, а именно: особенности социального
развития городских и сельских территорий, определение целей, индикаторов и факторов этого
процесса.
Ключевые слова: социальное развитие, старопромышленные регионы, общественно-географические
исследования, депрессивные регионы. The list of geographers involved in investigations of depressed areas of urban and countryside social
and geographic systems at old industrial regions is not long. Besides, analysis of research papers by both
Ukrainian and Russian geographers allows stating that the degree of geographic investigation in old industrial
regions is about zero including their social development from the viewpoint of social geography. There is no
doubt that the ground for effective regional policy formation means consideration of social and geographic
processes of regional development with disclosure of their tendencies and laws. Thus one should note that
economists more than geographers deal with development of old industrial regions including social one. Based
upon the analysis of earlier investigations related to old industrial regions one could come to conclusion that
either status or tendencies of their social development are extremely unsatisfactory. The lack of detailed analysis
with urban and countryside social and geographic systems of these regions and consequently quality and
efficient administrative decisions in governmental regional social policy of Ukraine conditions the low level of
regions’ social development, further increase of interregional differentiation, appearance and escalation of
numerous social problems on regional level. In recent years some geographers demonstrate a certain progress
towards investigation of old industrial regions however in practice there is no one either in Ukraine or Russia to
deal with the sphere of social development of old industrial regions from the position of complex social and
geographic analysis taking into account both aims and factors of the sphere. Thus there exists a vital need in the
system approach to problems solution with old industrial regions including from the viewpoint of social
geography on identification of aims, indicators, and factors of their social development.
Key words: social development, old industrial regions, social and geographical investigations, depressed
regions.